PERAN GURU BK DALAM MENGATASI ANAK YANG BELUM PANDAI MEMBACA DI DESA BUKIT CERMIN HILIR - Ayu Ari Lestari; Nuria Ariefah Nanda; Andini Amayanthi Purba; Dina Indriyani; Ivo Liza Miranda; Husnul Fatimah; Alfin Siregar (STKIP Subang, 2023)
Education plays a crucial role in shaping the character and quality of human resources. One of the essential skills is the ability to read, which not only provides access to knowledge but also influences critical thinking and problem-solving skills. Bukit Cermin Hilir Village, as part of a developing community, faces specific challenges in education, particularly in the context of reading. Difficulty in reading can adversely affect the comprehension of study materials and academic performance among children. The role of Guidance and Counseling Teachers (BK) is vital in addressing these challenges. With a profound understanding of the psychological needs and development of children, BK Teachers can design effective intervention strategies to enhance the reading abilities of children in Bukit Cermin Hilir Village. This research aims to explore and analyze the role of BK Teachers in dealing with children who are not yet proficient in reading in this village. The study adopts a qualitative approach with field research methods. Data are collected through observation, interviews, and documentation in Bukit Cermin Hilir Village. The research endeavors to identify concrete solutions and practical recommendations to improve literacy levels among children in this village. The collaborative efforts are expected to contribute positively to enhancing the quality of education and the future prospects of children in Bukit Cermin Hilir Village.